1993
DOI: 10.1128/mcb.13.2.739
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the erythropoietin receptor and the Friend spleen focus-forming virus gp55 glycoprotein transforms a factor-dependent hematopoietic cell line.

Abstract: The Friend spleen focus-forming virus (SFFV) gp55 glycoprotein binds to the erythropoietin receptor (EPO-R), causing constitutive receptor signaling and the first stage of Friend erythroleukemia. We have used three independent strategies to further define this transforming molecular interaction. First, using a retroviral selection strategy, we have isolated the cDNAs encoding three fusion polypeptides containing regions of both EPO-R and gp55. These fusion proteins, like full-length gp55, transformed the Ba/F3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…We initially synthesized cDNA encoding a truncated form of murine EPO-R [EPO-R(T)], which lacks the critical signaltransducing domain previously described (13,17,30) was transfected into the ecotropic packaging cell line, E86, and a helper-free stock of PLSXN-EPO-R(T) was generated (38). The expression of full-length EPO-R and EPO-R(T) in infected Ba/F3 cells was confirmed by FACScan analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We initially synthesized cDNA encoding a truncated form of murine EPO-R [EPO-R(T)], which lacks the critical signaltransducing domain previously described (13,17,30) was transfected into the ecotropic packaging cell line, E86, and a helper-free stock of PLSXN-EPO-R(T) was generated (38). The expression of full-length EPO-R and EPO-R(T) in infected Ba/F3 cells was confirmed by FACScan analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the bulk of the interaction between F-gp55 and EPO-R occurs in an intracellular compartment (44), the complex of F-gp55 and EPO-R has also been detected at the cell surface (5,16). We next tested EPO-R(T) for its ability to block F-gp55-mediated activation of wild-type EPO-R. Parental Ba/F3 cells, Ba/F3-EPO-R cells, or Ba/F3-EPO-R-EPO-R(T) cells were infected with a retrovirus encoding F-gp55 (38). Infected subclones were isolated by limiting dilution and analyzed for IL-3-dependent or EPO-dependent growth ( 3).…”
Section: Epo-r Cells) Expressed Low Levels Of Epo-r Ba/f3 Cells Infementioning
confidence: 99%
See 1 more Smart Citation
“…The murine EPOR, but not the human EPOR, is able to support gp55 P -mediated Ba/F3-cell proliferation. 31 Indeed, the structural basis for this difference has been localized to a single amino acid in the transmembrane domain of the EPOR. 36 We found that mice expressing the human EPOR instead of the murine EPOR were fully susceptible to Friend virus-induced erythroblastosis.…”
Section: Discussionmentioning
confidence: 99%
“…The human EPOR is ineffective in this context. 31 We studied mice with a targeted mutation of the murine Epor that were transgenic for the human EPOR (Epor Ϫ/Ϫ ;Tg(EPOR)). 21 …”
Section: The Murine Epor Is Not Required For Friend Virus-induced Erymentioning
confidence: 99%